Competitive information disclosure in random search markets - HE, Wei (Institutional Knowledge at Singapore Management University, 2021)
We analyze the role of competition in information provision in random search markets. Multiple symmetric senders compete for the receiver’s investment by disclosing information about their respective project qualities, and the receiver conducts random search to learn about the qualities of the projects. We show that in any symmetric Nash equilibrium, each sender chooses a strategy with the lowest possible reservation value. The receiver does not benefit from the competition of the senders, as the receiver’s expected payoff does not change when the number of senders increases.